Aspects of the Serum Biochemistry, Carcass Quality and Organoleptic Characteristics of Broilers Fed Alkali-Treated Date Pits - Al-Bowait, M.; Al-Sultan, S.I. (International Journal of Poultry Science, 2006)
The effects of feeding alkaline treated date pits (TDP) on serum biochemistry, carcass quality and organoleptic characteristics were investigated in 396 commercial broiler chicks of the Hybro strain. The values of glucose, albumin, protein, calcium, pH and GPT and GOT showed no significant difference when compared with the values obtained from the control broilers (feed on corn). Similarly no significant difference was obtained in the values of the meat composition, carcass quality, visceral and abdominal fat between the treated and control broiler. Sensory evaluation parameters of cooked meat were highly accepted to panelists. Replacement corn with alkaline treated date pits as high as 62.4% in broilers diets did not produce serous adverse affects on performance, serum biochemistry, carcass and eating quality of broilers.